Using Ethno-Pedagogy to Prepare Students for Civic Education in the Society 5.0 Era - Wardani, Helda Kusuma; ., Nuphanudin; Saadatul Ummah, Fiena; Hadi, Ahmad Safiie (KnE Social Sciences, 2024)
This paper is the outcome of a review of the literature on ethno-pedagogy and education in the context of Society 5.0, gathered from various online reports, digital books, and journal articles. Society 5.0 can leverage technology in education to offer more individualized and interactive learning experiences. Examples include online learning and the application of augmented and virtual reality (AR and VR) to the classroom. Education must be adequately prepared in this day and age to assist people in gaining the abilities and knowledge required to meet obstacles in the future. In order to prepare education for the Society 5.0 era, this article aims to investigate the ethno-pedagogy method in greater detail. We refer to this method of teaching based on culture as ethno-pedagogy. The technique is highly pertinent to educating students for the increasingly varied and complicated Society 5.0 era. Using this method enables educators to create a curriculum that honors the cultural values of their students. Technology has the potential to be a helpful tool in the implementation of ethno-pedagogy. Keywords: educational management; ethno-pedagogical approach; Society 5.0 era